Perang Sidobunder Sebagai Upaya Mempertahankan Kemerdekaan Tahun 1947 - sita salsabilla (KARMAWIBANGGA: Historical Studies Journal, 2022)
This study aims to: (1) describe the condition of the Kebumen region during the independence era; (2) describe the process of Sidobunder War in Kebumen in 1947; (3) describe the impact of the Sidobunder War in Kebumen 1947. This study uses literature review method. Data collection in this study was carried out by collecting written sources such an books, journal, thesis and internet related with a theme discussed by the author. The steps in this study is heuristics, source critism or verification, interpretation and historiography.The results of this study are: (1) Kebumen which is included in the residency of Kedu with the livelihood of the population is farming; (2) Sidobunder War is a war that occurs between student soldiers and the Dutch that means to defend independence; (3) Sidobunder War impact on student soldiers, the Dutch, and the unity of the Republic of Indonesia